2017
DOI: 10.4103/ijmy.ijmy_26_17
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of putative efflux pump genes to isoniazid resistance in clinical isolates of Mycobacterium tuberculosis

Abstract: The high number of efflux genes overexpressed in an INH-resistant isolate with no known INH resistance associated mutations, suggests a role for efflux pumps in resistance to this antituberculous agent, with the role of Rv0194 and Rv0507 in INH resistance being reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 1 publication
0
12
1
Order By: Relevance
“…Contrary to our findings, Narang et al reported that Rv1250 and Rv876 were not overexpressed in any of the MDR isolates due to INH stress [9]. In this study, we revealed that among mono-resistant isolates, only were Rv1250 and Rv876 co-overexpressed in the PII-7 isolate in response to RIF.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Narang et al reported that Rv1250 and Rv876 were not overexpressed in any of the MDR isolates due to INH stress [9]. In this study, we revealed that among mono-resistant isolates, only were Rv1250 and Rv876 co-overexpressed in the PII-7 isolate in response to RIF.…”
Section: Discussioncontrasting
confidence: 99%
“…Other mechanisms of resistance, such as efflux pumps, act synergistically with the permeability barrier to reduce the passage of antimicrobials across the bacterial outer membrane [8]. Previous studies have demonstrated that the resistance of M. tuberculosis is associated with constitutive or inducible expression of efflux systems [9, 10]. Efflux pumps utilize the transmembrane electrochemical gradient of protons or sodium ions to extrude drugs from the cell, thereby neutralizing drug activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The other genes do not appear to have any link with the biosynthesis of these fatty acids, but may be induced because of the toxic effects of isoniazid. Moreover, upregulation of the expression of the gene efpA , which encodes a major facilitator superfamily (MFS) efflux pump, as well as the upregulation of iniA , which encodes putative pump component, could participate in intrinsic resistance to isoniazid, as has been reported in other studies (Colangeli et al, 2005; Gupta et al, 2010; Li et al, 2015; Narang et al, 2017). iniA is upregulated along with iniB and iniC , these genes are indeed organized in operon under the control of iniBAC promoter and upregulated by various cell envelope inhibitor (Alland et al, 1998, 2000).…”
Section: Isoniazid Induced Changes In Gene Expressionmentioning
confidence: 53%
“…Major facilitator superfamily (MFS) [40] Isoniazid Rv1272c-1273c ATP-binding transport protein family (ABC transporters) [33] Isoniazid, tetracycline, rifampicin and clofazimine Rv1410c (p55) Major facilitator superfamily (MFS) [33,37] Isoniazid, Rifampicin, Ethambutol, Streptomycin Rv1458c, Rv1457c, Rv1456c…”
Section: Rv1258cmentioning
confidence: 99%